2016
DOI: 10.1523/jneurosci.3047-16.2016
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal α-Synuclein in Dementia with Lewy Bodies Contributes to Memory Impairment and Is Consistent with Spread of Pathology

Abstract: Despite considerable research to uncover them, the anatomic and neuropathologic correlates of memory impairment in dementia with Lewy bodies (DLB) remain unclear. While some studies have implicated Lewy bodies in the neocortex, others have pointed to ␣-synuclein pathology in the hippocampus. We systematically examined hippocampal Lewy pathology and its distribution in hippocampal subfields in 95 clinically and neuropathologically characterized human cases of DLB, finding that ␣-synuclein pathology was highest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
63
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(80 citation statements)
references
References 65 publications
16
63
1
Order By: Relevance
“…Of all cornu Ammonis hippocampal fields, the small CA2 subregion displays the earliest and densest Lewy pathology in both PD and DLB . According to our previous work and the present study, the earliest and densest hippocampal pathology in fibril‐infused mice was not in CA2, but centered in ventral CA1 and the subiculum, consistent with the dense retrograde labeling of these two structures following FluoroGold infusions in the OB/AON complex and with a large body of work on the afferents of anterior olfactory brain regions (eg, see Table 2 in ) .…”
Section: Discussionsupporting
confidence: 89%
“…Of all cornu Ammonis hippocampal fields, the small CA2 subregion displays the earliest and densest Lewy pathology in both PD and DLB . According to our previous work and the present study, the earliest and densest hippocampal pathology in fibril‐infused mice was not in CA2, but centered in ventral CA1 and the subiculum, consistent with the dense retrograde labeling of these two structures following FluoroGold infusions in the OB/AON complex and with a large body of work on the afferents of anterior olfactory brain regions (eg, see Table 2 in ) .…”
Section: Discussionsupporting
confidence: 89%
“…The majority of studies have found that PDD is associated with either limbic (transitional) or neocortical (diffuse) stage LB pathology with higher cortical LP density being observed than in nondemented PD . Neocortical LP is also associated with the onset of visual hallucinations, and hippocampal SYN pathology is associated with memory deficits even after controlling for age and co‐occurring pathologies . The current neuropathological assessment of DLB recognizes that cases with pure synucleinopathy without AD copathology are the most likely to exhibit core DLB features or visual hallucinations and fluctuations .…”
Section: The Role Of Alpha‐synuclein In Lbd Pathogenesismentioning
confidence: 99%
“…PD. PD and dementia with Lewy bodies (DLB) frequently overlap with AD (Adamowicz et al, 2017;Hansen et al, 1993;Tsuboi and Dickson, 2005). For instance, in hippocampi of PD (DLB) patients, intracellular a-synuclein pathology frequently coincides with Ab and tau pathologies.…”
Section: Insulin Resistancementioning
confidence: 99%